The social crusader : James Gibb at the Australasian pastoral frontier, 1882-1935 : a thesis presented in partial fulfilment of the requirements of the degree of Doctor of Philosophy in History at Massey University - Barber, Lawrence Harold (Massey University, 1975)
The phrase 'pastoral frontier' is generally used to identify the periphery of farm settlement; the advancing borderland between territory newly won by farmers and a region of untamed virgin land. This thesis is concerned with a different 'pastoral frontier', although related to the former. Using the term 'pastoral' as indicative of the ministrations of priests and ministers to their flocks, this 'pastoral frontier' is the ever changing border area where the Church penetrates society and society re-shapes the Church. The key figure is James Gibb, who led the Presbyterian Church of New Zealand for over three decades; a Scot who came to Otago after a short ministry in Victoria, and a pastor who faced the 'pastoral frontier' for fifty-three years. Gibb was a church leader par excellence; founding father of a national Presbyterian Church, Moderator, pioneer of social services and founder of church schools. He was a social crusader who emphasised a social ethic and social redemption. His Scottish Presbyterian conviction that the Church was duty-bound to transform the state into a Christian commonwealth led him into a series of public campaigns and political encounters that had as their goal the making of a less sinful New Zealand. This thesis argues that Gibb adapted the Social Gospel, the new social interpretation of Christianity emphasised by European, British and American theologians from the close of the nineteenth century, to the New Zealand 'pastoral frontier'. His central role in church affairs, and his placement as a campaigner and lobbyist in the political field, allow an assessment of his successes and failures as a social crusader to indicate the successes and failures of the New Zealand Protestant churches in their attempts to penetrate national life and mould society to their own design. The rise and fall of Gibb's social crusades reflect the rise and fall of the Social Gospel in New Zealand. Gibb's 'pastoral frontier' was not static and during his Australasian ministry he planted his social crusading flag at three frontiers:- 1. A Limited Frontier, 1882-1903. 2. An Expanded Frontier, 1903-1922. 3. A Contracted Frontier, 1923-1935. 1. A Limited Frontier, 1882-1903 This frontier was circumscribed by the narrow boundaries of Presbyterian interest and opportunity in Victoria and Otago. In the Presbyterian Church of Victoria Gibb found himself embroiled in a fierce conflict between theological revisionists and Calvinist Confessionalists. His ministry in Melbourne was dominated by the Charles Strong affair. In Otago he found himself in a provincial church planted by Free Church of Scotland ministers who lived in the mental climte of the Scottish Disruption of 1843. A provincial perspective, the rigid confessionalism of an imported theology, and attempts to impose Calvinist social controls over marriage, Sabbath observance, drinking and dancing, were the hall-marks of this Church's impact on society. Gibb's leadership of the Bible-in-Schools movement was prompted by a-concern to make the state education system accept Biblical studies as a foundation for all other knowledge. Between 1886 (when he arrived in Otago) and 1902 Gibb and his Church were not entirely dominated by intra-mural concerns but they were mainly concerned with polishing thsir denominational badge and attaching it to others. Towards the close of this period a developing sense of national identity aided Gibb in creating the united Presbyterian Church of New Zealand yet even then some of his Otago supporters were more concerned with Presbyterian hegemony than with the challenge posed by the creation of a national church. 2. An Expanded Frontier, 1903-1922 The 'pastoral frontier' expanded dramatically from 1903. Gibb responded with a more self-conscious programme of nation building. He failed in his attempt to manufacture one national Protestant Evangelical church, incorporating the nation's Presbyterians, Methodists, and Congregationalists. He succeeded in planting a Presbyterian minister and agent in almost every settlement, in town and back-blocks, and broke with traditional Scottish Church polity in so doing, by creating a new order of ministers-home missionaries. This expanded frontier extended to the Pacific Islands and into China with Gibb leading petitions for British control of the New Hebrides and attacking the opium trade to China. The Church still demanded the right to legislate national social control and crusades in favour of prohibition and Bible-in-Schools grew in intensity and impact, with Gibb encouraging back-block ministers to rasp-off pioneer rough edges and polish colonial rough diamonds. The 1914-1918 war brought conflict within the Church as imperial patriotism and Christian principles met in tension. Consolidation of settlement and post-war despair and failure to return to 'normalcy' ended an era of self confidence. 3. A Contracted Frontier, 1923-1935 From 1923 the 'pastoral frontier' began to steadily contract. The 'crusades' - Bible-in-Schools, Prohibition, Disarmament, and a united Protestant Church - all failed. The Church's national impact was further weakened by her failure to prevent increasing economic and political polarization within society, her failure to convince an increasingly mobile and pleasure-seeking society, her failure to create a disciplined and coherent national Church, the decline in dynamic that followed the closing of the internal frontier, state acceptance of social service roles, the impact of Barthian theology, and her inability to hold back or accommodate the flood of secularism.
Keywords: James Gibb; Presbytarian Church; History; Australia; New Zealand